2012
DOI: 10.1136/bmj.e3750
|View full text |Cite
|
Sign up to set email alerts
|

Internet based vascular risk factor management for patients with clinically manifest vascular disease: randomised controlled trial

Abstract: Objective To investigate whether an internet based, nurse led vascular risk factor management programme promoting self management on top of usual care is more effective than usual care alone in reducing vascular risk factors in patients with clinically manifest vascular disease. Design Prospective randomised controlled trial.Setting Multicentre trial in secondary and tertiary healthcare setting.Participants 330 patients with a recent clinical manifestation of atherosclerosis in the coronary, cerebral, or perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 35 publications
(41 reference statements)
2
49
0
1
Order By: Relevance
“…For lack of a validated risk function in secondary prevention, we selected the SCORE function for 10-year cardiovascular risk as the primary outcome in our secondary prevention trial. A recently published, comparable trial has similarly used a primary prevention risk score as the main outcome measure to quantify the effect of a secondary prevention programme 16. Although the absolute estimates of the SCORE function are inaccurate in secondary prevention, the difference in SCORE between the two groups provides an estimate of the relative overall impact of a risk factor intervention.…”
Section: Discussionmentioning
confidence: 99%
“…For lack of a validated risk function in secondary prevention, we selected the SCORE function for 10-year cardiovascular risk as the primary outcome in our secondary prevention trial. A recently published, comparable trial has similarly used a primary prevention risk score as the main outcome measure to quantify the effect of a secondary prevention programme 16. Although the absolute estimates of the SCORE function are inaccurate in secondary prevention, the difference in SCORE between the two groups provides an estimate of the relative overall impact of a risk factor intervention.…”
Section: Discussionmentioning
confidence: 99%
“…61 A more recent study from the Netherlands reported the findings of an online nurse practitioner-supported intervention for vascular risk management in patients with clinically manifest vascular disease. 376 Although…”
Section: Relationship To Previous Researchmentioning
confidence: 99%
“…However, our study setting closely resembles the United Kingdom National Health Service and integrated managed care organizations in the United States, and the clinical profiles of our participants were similar to recent reports of stroke survivors from other Canadian provinces, the US, the UK and Europe. 1,2,10,20,24,25,28 When considering the external validity of our results, the under-treatment of vascular risk factors is a nearly universal phenomenon and has been documented in many other settings and for other atherosclerotic conditions.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…15,20 Although 2 recent trials 21,22 involving younger patients with uncontrolled hypertension reported similar systolic blood pressure reductions and blood pressure control rates with the involvement of pharmacist case managers, our study enrolled older higher-risk patients with lower systolic blood pressure at baseline; we also assessed the impact of a pharmacist case manager on a wider array of vascular risk factors. The observed reductions in systolic blood pressure in the nurse-led active control group were just as large as those in the pharmacist case manager group, which is consistent with our previous findings about the efficacy of our nurse-led active control intervention for blood pressure reduction.…”
Section: Researchmentioning
confidence: 99%